Host galaxies of merging compact objects: mass, star formation rate, metallicity, and colours. Issue 2 (20th May 2019) - Artale, M Celeste; Mapelli, Michela; Giacobbo, Nicola; Sabha, Nadeen B; Spera, Mario; Santoliquido, Filippo; Bressan, Alessandro
Abstract: Characterizing the properties of the host galaxies of merging compact objects provides essential clues to interpret current and future gravitational-wave detections. Here, we investigate the stellar mass, star formation rate (SFR), metallicity, and colours of the host galaxies of merging compact objects in the local Universe by combining the results of mobse population-synthesis models together with galaxy catalogues from the eagle simulation. We predict that the stellar mass of the host galaxy is an excellent tracer of the merger rate per galaxy nGW of double neutron stars (DNSs), double black holes (DBHs), and black hole–neutron star binaries (BHNSs). We find a significant correlation also between nGW and SFR. As a consequence, nGW correlates also with the r -band luminosity and with the g − r colour of the host galaxies. Interestingly, ≳60 per cent, ≳64 per cent, and ≳73 per cent of all the DNSs, BHNSs, and DBHs merging in the local Universe lie in early-type galaxies, such as NGC 4993. We predict a local DNS merger rate density of ∼238 Gpc −3 yr −1 and a DNS merger rate ∼16–121 Myr −1 for Milky Way-like galaxies. Thus, our results are consistent with both the DNS merger rate inferred from GW170817 and the one inferred from Galactic DNSs.